Conventional Coronary Angiography Induced Takotsubo Cardiomyopathy Complicated with Cardiac Tamponade. (1st March 2017) - Kang, Min Gyu; Kim, Kye-Hwan; Koh, Jin-Sin; Jeong, Young-Hoon; Hwang, Jin-Yong; Park, Jeong Rang
Abstract : Takotsubo cardiomyopathy (TCM) is a transient left ventricular dysfunction that typically occurs after emotional or physical stress. TCM has a benign prognosis and serious complications are uncommon. However, though very rarely reported, cardiac tamponade has occurred on some occasions. We hereby report the case of a 70-year-old woman who underwent coronary angiography with an ergonovine provocation test to evaluate recurrent chest pain and was readmitted 7 days later presenting with TCM, followed by left ventricular outflow tract obstruction and cardiac tamponade.